Co-infection of long-term carriers of Plasmodium falciparum with Schistosoma haematobium enhances protection from febrile malaria: a prospective cohort study in Mali. - Safiatou Doumbo; Tuan M Tran; Jules Sangala; Shanping Li; Didier Doumtabe; Younoussou Kone; Abdrahamane Traoré; Aboudramane Bathily; Nafomon Sogoba; Michel E Coulibaly; Chiung-Yu Huang; Aissata Ongoiba; et al. (Public Library of Science (PLoS), 2014)
Malaria and schistosomiasis often overlap in tropical and subtropical countries and impose tremendous disease burdens; however, the extent to which schistosomiasis modifies the risk of febrile malaria remains unclear.We evaluated the effect of baseline S. haematobium mono-infection, baseline P. falciparum mono-infection, and co-infection with both parasites on the risk of febrile malaria in a prospective cohort study of 616 children and adults living in Kalifabougou, Mali. Individuals with S. haematobium were treated with praziquantel within 6 weeks of enrollment. Malaria episodes were detected by weekly physical examination and self-referral for 7 months. The primary outcome was time to first or only malaria episode defined as fever (≥ 37.5 °C) and parasitemia (≥ 2500 asexual parasites/µl). Secondary definitions of malaria using different parasite densities were also explored.After adjusting for age, anemia status, sickle cell trait, distance from home to river, residence within a cluster of high S. haematobium transmission, and housing type, baseline P. falciparum mono-infection (n = 254) and co-infection (n = 39) were significantly associated with protection from febrile malaria by Cox regression (hazard ratios 0.71 and 0.44; P = 0.01 and 0.02; reference group: uninfected at baseline). Baseline S. haematobium mono-infection (n = 23) did not associate with malaria protection in the adjusted analysis, but this may be due to lack of statistical power. Anemia significantly interacted with co-infection (P = 0.009), and the malaria-protective effect of co-infection was strongest in non-anemic individuals. Co-infection was an independent negative predictor of lower parasite density at the first febrile malaria episode.Co-infection with S. haematobium and P. falciparum is significantly associated with reduced risk of febrile malaria in long-term asymptomatic carriers of P. falciparum. Future studies are needed to determine whether co-infection induces immunomodulatory mechanisms that protect against febrile malaria or whether genetic, behavioral, or environmental factors not accounted for here explain these findings.